Application of Shared Decision-making in the Diagnosis and Treatment of Parotid Tumors - Rui ZHANG; Gang CHEN (Yixue yu zhexue)
Through the analysis of the clinical application effects of shared decision-making (SDM) model in the diagnosis and treatment of parotid tumors within oral and maxillofacial surgery, this study aims to deepen the understanding of various forms of collaborative decision-making, including doctor-patient co-decision making, doctor-patient-family co-decision making, and multidisciplinary team-based decision making. In clinical practice, emphasizing SDM process can significantly enhance patient and family engagement while promoting the equitable SDM authority of SDM, thereby enabling the development of personalized and precise diagnostic and therapeutic strategies. The application characteristics of SDM in oral and maxillofacial surgery were systematically summarised based on patients' educational backgrounds, family circumstances, and multidisciplinary diagnosis and treatment recommendations, with the goal of enhancing the competence of oral and maxillofacial surgeons in implementing SDM.